(untitled) (Mūzikas akadēmijas raksti, 2024)
The irony is that vocalizes for the choir by Jānis Ivanovs (1906–1983), not being solitary in the creative contribution of his own within the context of Latvian music as such still seem to be slightly alien and incongruous. They remain marginal even in the confines of choral singing owing to both the complicacy of musical writing that is beyond the capacity of a considerable part of the choirs and the lack of the text, the latter being non-traditional and even embarrassing to the audience. The text of a choral song proves to be a force of tremendous power, consolidating the singers and the public in one common idea, attitude and poetics. However, the text also sets particular restrictions, directing imagery into a verbally determined expression, even being stylistically very unconfined. For such a composer whose way of thinking manifests itself in purely musical categories, considerably devoid of fully or semiprogrammatic denominations, explanations or commentary, the genre of vocalize has proved to be fascinating just because of its freedom, enabling communication with the scope and magic of choral singing, at the same time being dominant in the choice and development of the music of his own.